Finger Painting to Improve Fine Motor Skills Children Aged 4-5 Years - Hanna, Tsania Qurrotaainin; Zulkarnaen, Z (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the process and results of improving children's fine motor skills through finger painting activities at Sahabat Early Childhood Education Center, Colomadu, Karanganyar. This research was conducted due to the need for better stimulation of fine motor skills, as previous methods were less interesting and lacked variety. The method used was qualitative with a collaborative approach, which included observation, interviews, and collective documentation. This study involved six children aged 4–5 years and two educators. The criteria for measuring fine motor skills included three aspects, namely (1) pattern formation, (2) shape conformity, and (3) finger flexibility. The results showed that finger painting activities were very effective in improving children's fine motor skills. Of the six children involved, four (67%) fell into the